Oxidation heat effects of metal nanopowders after electron irradiation; International Multidisciplinary Scientific GeoConference Surveying Geology and Mining Ecology Management; Vol. 1, № 6 - Dilmukhambetov E. E.; Espolov T.; Ospanova M.; Ilyin A. P. Aleksandr Petrovich (2014, 2014)
The nanopowders of iron, nickel, molybdenum and copper received by electric explosion of wire were irradiated by an electron current on the liner electron accelerator with the radiation doses of 1, 5, 10 Mrad. Four parameters of activity of nanopowders were evaluated according to the differential thermal analysis: the initial temperature of oxidation, the completeness of oxidation, the maximum speed of metal oxidation and the thermal effect of oxidation. It was ascertained that the thermal effect of combustion increased after irradiation by 1.5-2.5 times. It was shown that the significant increase of the heat of combustion of nanopowders was caused by the increase of the internal stored energy as a result of the ionizing effect of electrons. The electrostatic model of surface charged structures of nanoparticles generated by the ionizing effect of electrons was offered, and its analogue is a spherical capacitor. This model makes it possible to estimate the increase of the surface energy of nanopowders by charging the spherical nanocapacitor with 110-1 100 kJ/mol. It was shown that the lattice parameters of the initial and irradiated metal nanopowders are greater than those of the standard samples of massive metals. Irradiation of nanopowders by accelerated electrons furthers stabilization of interplanar spacings of crystal lattices and brings them closer the standard of massive metals.